Work Function Maps and Surface Topography Characterization of Nitroaromatic-Ended Dendron Films on Graphite. (28th October 2013) - Farías, Eliana D.; Brunetti, Verónica; Paez, Julieta I.; Strumia, Miriam C.; Passeggi, Mario C.G.; Ferrón, Julio
Abstract Surface topography and work function maps were simultaneously obtained for carbon surfaces modified by a dendritic molecule: 3, 5-Bis (3, 5-dinitrobenzoylamino) benzoic acid. The dendrons were spontaneously assembled onto highly ordered pyrolytic graphite samples, exhibiting an increase in the surface potential. This fact is consistent with the incorporation of an electron-acceptor functional group that remains electroactive on the surface.